Pengaruh Return On Assets (ROA), Net Profit Margin (NPM), Earning Pershare (EPS) Dan Total Assets Turn Over (TATO) Terhadap Return Saham Pada Sektor Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Andre Reymon Nirwana; Dicky Jhoansyah; Erry Sunarya (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study was to determine the analysis of Return on Assets, Net Profit Margin, Earning Per-Share, Total Assets Turnover, measure the effect of Return on Assets, Net Profit Margin, Earning Per-Share, and Total Assets Turnover on Stock Return. Researchers used a quantitative approach with descriptive and associative methods. The sample companies in this study amounted to 8 companies. The analytical technique used in this research is descriptive and inferential analysis statistical analysis through linear regression analysis for hypothesis testing. Based on research results obtained, the ROA value of manufacturing companies generally tends to be above the industry standard average, the NPM value of manufacturing companies generally tends to be below the industry standard average, the EPS value of all companies has a positive value. Thus, manufacturing companies during the 2016-2020 period have the advantage of each share, the TATO value of manufacturing companies generally tends to be below the industry standard average, Something positive and insignificant Asset Return effect (ROA), negative and insignificant effect of Net Profit Margin (NPM) on Stock Return, There is a positive and significant effect of Earning Per-Share (EPS) on Stock Return, and there is a negative and insignificant effect of Total Asset Turnover (TATO) on Stock Return . Keyword : Return on Assets, Net Profit Margin, Earning Per-Share, Total Assets Turnover and Stock Return.